Emotional openness as an affective norm in representations of Gen Z masculinity on TikTok - Firna Sayyidatul Qurroh 'Aini; Nur'annafi Farni Syam Maella; Zulaikha Zulaikha (COMMICAST, 2026)
This study examines the representation and normalization of emotional openness as an affective norm in Gen Z masculinity on TikTok, focusing on the fineshyt content trend. Using a qualitative discourse analysis approach, the study analyzes 15 TikTok videos featuring emotional expression by male Gen Z creators and 436 audience comments purposively selected based on affective relevance. Data were collected between August - October 2025 and examined to identify patterns of emotional expression and audience interaction.  The findings show that emotional openness is not articulated solely as individual expression but is collectively legitimized through audience responses that function as affective validation. Three dominant patterns of audience response emerge: affirmative appreciation of emotionally open masculinity, resistance grounded in traditional masculine norms, and relational fantasies that frame emotional openness as affective appeal. These interactions indicate a contextual shift in the representation of masculinity within specific TikTok content, where emotional expression is positioned as socially acceptable rather than as a sign of weakness.  While previous studies on digital masculinity have primarily focused on male self-representation, this study highlights the central role of audience interaction in shaping and normalizing emotional expression. This study extends existing masculinity and digital communication scholarship by conceptualizing emotional openness not merely as individual expression, but as an affective norm co-produced through audience interaction. By positioning the comment section as a site of affective negotiation, this research contributes to a deeper understanding of how gender norms are constructed within participatory digital environments.